Fluorinated Pseudopeptide Analogues of the Neuropeptide 26RFa: Synthesis, Biological, and Structural Studies. Issue 13 (12th August 2013) - Pierry, Camille; Couve‐Bonnaire, Samuel; Guilhaudis, Laure; Neveu, Cindy; Marotte, Amélie; Lefranc, Benjamin; Cahard, Dominique; Ségalas‐Milazzo, Isabelle; Leprince, Jérôme; Pannecoucke, Xavier
Abstract A series of four fluorinated dipeptide analogues each containing a fluoro‐olefin moiety as peptide bond surrogate has been designed and synthesized. These motifs have been successfully introduced into the bioactive C‐terminal heptapeptide of the neuropeptide 26RFa by conventional SPPS. We then evaluated the ability of the generated pseudopeptides to increase [Ca2+]i in GPR103‐transfected cells. For these fluorinated analogues, greater stability in human serum was observed. Their conformations were also investigated, leading to the valuable identification of differences depending on the position of the fluoro‐olefin moiety in the sequence.